Constraints to Learning Science with an Online Learning System in the Era of the Covid-19 Pandemic - Sabila Yasaroh; Jumadi Jumadi; Hestiana Hestiana (Pendidikan Kimia Unimus, 2022)
This study explored the constraints of learning science with an online learning system (on the network) in the era of the Covid-19 pandemic. This research design was descriptive qualitative with a phenomenological approach. Phenomenology is an effort that aims to explain something that occurs according to reality. Data was collected through questionnaires open to SMP/MTs students and semi-structured interviews with student parents. The data analysis technique in this study used data Qualitative data that were presented without numerical calculations. The study results showed that learning science with the online method encountered many obstacles. The barriers to learning science with online methods referred to three important aspects, namely differences in student learning style, technological literacy, and parental support.